The fundamental right to a due process versus the Peruvian Administrative proceeding - Jiménez Vivas, Javier Eduardo (2019)
This assay presents the due process of law as a constitutionalized human right facing the Peruvian administrative proceeding. It describes the road traveled by the former up to its ultimate acknowledgement, in the administrative law, through the different regulatory, doctrinarian and jurisprudential instruments. It shows the present consolidation of said right in an administrative headquarters and offers clues for its future interpretation and attention, from the national and compared viewpoint.